Transcriptional progression during meiotic prophase I reveals sex-specific features and X chromosome dynamics in human fetal female germline. - Xueying Fan; Ioannis Moustakas; Vanessa Torrens-Juaneda; Qijing Lei; Geert Hamer; Leoni A Louwe; Gonneke S K Pilgram; Karoly Szuhai; Roberto Matorras; Cristina Eguizabal; Lucette van der Westerlaken; Hailiang Mei; et al. (PLoS Genetics)
During gametogenesis in mammals, meiosis ensures the production of haploid gametes. The timing and length of meiosis to produce female and male gametes differ considerably. In contrast to males, meiotic prophase I in females initiates during development. Hence, the knowledge regarding progression through meiotic prophase I is mainly focused on human male spermatogenesis and female oocyte maturation during adulthood. Therefore, it remains unclear how the different stages of meiotic prophase I between human oogenesis and spermatogenesis compare. Analysis of single-cell transcriptomics data from human fetal germ cells (FGC) allowed us to identify the molecular signatures of female meiotic prophase I stages leptotene, zygotene, pachytene and diplotene. We have compared those between male and female germ cells in similar stages of meiotic prophase I and revealed conserved and specific features between sexes. We identified not only key players involved in the process of meiosis, but also highlighted the molecular components that could be responsible for changes in cellular morphology that occur during this developmental period, when the female FGC acquire their typical (sex-specific) oocyte shape as well as sex-differences in the regulation of DNA methylation. Analysis of X-linked expression between sexes during meiotic prophase I suggested a transient X-linked enrichment during female pachytene, that contrasts with the meiotic sex chromosome inactivation in males. Our study of the events that take place during meiotic prophase I provide a better understanding not only of female meiosis during development, but also highlights biomarkers that can be used to study infertility and offers insights in germline sex dimorphism in humans.